The Broadband Futures Forum: The Australian Broadband Advisory Council Agri-Tech Expert Working Group Report - Waters, Peter; Koch, Andrea (Journal of Telecommunications and the Digital Economy, 2022)
On 21 October 2021, TelSoc hosted the tenth Broadband Futures Forum, held online, to discuss a report by the Australian Broadband Advisory Council (ABAC) on the future of Agricultural Technology (Agri-Tech). After an introduction by the chair of ABAC, the two co-convenors of the ABAC Expert Working Group that produced the report outlined its content. Discussion following the speeches focussed particularly on the usefulness and efficiency of local solutions to extending wireless coverage, and the role of government and private investment in regional areas.